2018
DOI: 10.1007/s00234-018-2084-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined aspiration thrombectomy and continuous intrasinus thrombolysis for cerebral venous sinus thrombosis: technical note and case series

Abstract: Cerebral venous sinus thrombosis is an uncommon cause of stroke with high morbidity and mortality rates from venous infarction, intracranial hemorrhage, and extensive cerebral edema. Endovascular treatment with various devices has been proposed as a salvage treatment when standard medical treatment with systemic anticoagulation is ineffective, especially in long segment dural sinus thrombosis. We describe our technique of transvenous endovascular aspiration thrombectomy with large bore thrombectomy catheters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In addition, there have been some reports of the combined use of aspiration thrombectomy and intrasinus thrombolysis using a penumbra aspiration catheter. 12,13) Aspiration thrombectomy with a large-bore aspiration catheter using REACT 71 was reported by Sundar et al, 14) and may be a safe and effective treatment method for CVST.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there have been some reports of the combined use of aspiration thrombectomy and intrasinus thrombolysis using a penumbra aspiration catheter. 12,13) Aspiration thrombectomy with a large-bore aspiration catheter using REACT 71 was reported by Sundar et al, 14) and may be a safe and effective treatment method for CVST.…”
Section: Discussionmentioning
confidence: 97%
“…6 Randomized controlled trials focusing on alternative options after failure of standard of care are limited. There is scarce literature suggesting use of localized thrombolysis infusion leaving methods of patient selection, optimal time to intervene, contraindications to therapy, dose, and duration of therapy unclear (Table 2 5,[16][17][18][19][20] ). In general, if patient presents with very severe clot burden, deteriorates rapidly despite adequate anticoagulation, or demonstrates poor prognostic indicators such as rapid onset with coma and focal deficits or thrombosis affecting deep venous system, selective catheter-guided local thrombolysis may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review found a variety of dosing strategies with alteplase 1 mg per hour being the most commonly reported. 15,16,18 Compared to urokinase, alteplase is associated with lower bleeding complications due to clot selectiveness and shorter half-life. Unfortunately, the increase in ICP due to the thrombus places these patients at a high risk for bleeding which could be potentiated by the medications utilized to eliminate or manage the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular therapy has been found to be effective against CVST, but relevant research is mostly single-center and retrospective ( 6 – 9 ). Two systematic studies ( 10 , 11 ) on endovascular treatment for severe CVST and one randomized controlled trial ( 12 ) failed to find any advantage of endovascular therapy compared with anticoagulation therapy alone for patients with severe CVST.…”
Section: Introductionmentioning
confidence: 99%